2009
DOI: 10.1177/1527154409336200
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Working Conditions and Nursing Unit Costs

Abstract: The authors examined the relationship between nurse working conditions and nursing unit costs in 210 general medical, general surgical, and general medical surgical units in 112 randomly selected U.S. hospitals. Data were collected from registered nurses ( N = 3,747 and 2,878), patients ( N = 2,100), study coordinators, and secondary data sources. After controlling for relevant hospital, nursing unit, and patient characteristics, the authors found that good working conditions did not increase nursing unit cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
2
11
0
2
Order By: Relevance
“…Improving collegial relations among healthcare providers requires strong commitment from the hospital administrators, but may be achieved at little cost. 27 Previous research has demonstrated that hospitals could improve team collaborations via well-designed training programs that helped nurses and physicians understand their respective practice and expertise, responsibilities, and values. 28,29 A valid source for improving teamwork is the TeamSTEPPS program, which was developed by the Agency for Healthcare Research and Quality and the Department of Defense to improve communication and teamwork among healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Improving collegial relations among healthcare providers requires strong commitment from the hospital administrators, but may be achieved at little cost. 27 Previous research has demonstrated that hospitals could improve team collaborations via well-designed training programs that helped nurses and physicians understand their respective practice and expertise, responsibilities, and values. 28,29 A valid source for improving teamwork is the TeamSTEPPS program, which was developed by the Agency for Healthcare Research and Quality and the Department of Defense to improve communication and teamwork among healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…High-quality patient care depends on a nursing workforce that is empowered to provide care according to professional nursing standards [26] . Empowered nurses will certainly have the ability to resolve the patients' needs and their families' expectations and can effectively achieve their career and organizations goals [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Nurses are free to exercise their authority. So, autonomy plays an important part in nurses' job satisfaction and retention [8,9] .…”
mentioning
confidence: 99%
“…35,36 Esta situación es contraria a lo encontrado en Norteamérica, donde se les da participación en los procesos administrativos de la empresa, se promueve estrategias para retener a las enfermeras con estímulos de competencias profesionales, capacitaciones y cumplimiento de indicadores de productividad y seguridad para los pacientes y para las enfermeras. 12,13,[37][38][39] El estudio reporta menor calificación en la escala de ajuste, al compararla con la de adaptación. En la escala de ajuste, las enfermeras inicialmente hacen una reflexión personal y una calibración entre lo que la institución les ofrece y los intereses personales y expectativas laborales, esto es determinante para el logro de una adaptación positiva en la institución y la adherencia a las políticas, normas y protocolos.…”
Section: Escalas De Condiciones De Trabajo Y Organizaciónunclassified
“…[12][13] Para el caso de las enfermeras, estos entornos armoniosos de trabajo son un punto importante de intervención en la crisis del recurso humano en salud. 14 En Colombia las condiciones de trabajo, tradicionalmente, se han considerado desde las estructuras de la legislación laboral en el cubrimiento de estos cuatro componentes: a) La seguridad social integral (salud, pensión y riesgos profesionales), contemplada en la Ley 100 de 1993, b) las prestaciones sociales y el derecho a las vacaciones, c) los entornos o ambientes laborales seguros, y d) el desarrollo personal y social de los trabajadores.…”
Section: Introductionunclassified